Isolation of Lactobacillus rhamnosus from Human Breast Milk and Study their Susceptibility to Antibiotics - Shaimaa Ghanim Abdullah Alquraishi (Wasit Journal for Pure Sciences)
Probiotics have an assortment of implementations in various domains. Nowadays, probiotics are used as a method to prevention many disorders and  treat diseases. In this study was isolated  L.rhamnosus  from breast milk with the intention to studying  their properties as probiotics in view of important it on infant health.  24 positive samples out of 108 have been isolated and identification by using biochemical tests and molecular diagnosis using the 16S rRNA gene.  This research revealed relationship between pregnant period and existence of L.rhamnosus (P-Value  < 0.05). this relationship refers to the milk of mothers who have completed nine months of pregnancy had high percent of L.rhamnosus(75%) compared to mothers who delivery in seventh or eighth month of pregnancy whereas there no relationship ( P-Value  > 0.05)between existence of L.rhamnosus and mother age, infant age and type of delivery. The probiotic potential was assessed by determining antibiotic susceptibility through the disc diffusion method. Among the 24 isolates, resistance was observed to vancomycin and intermediate resistance to penicillin, streptomycin and clindamycin  respectively, while susceptibility was shown to ampicillin, tetracycline, chloramphenicol and gentamycin  respectively. Notably, none of the isolates exhibited hemolytic activity. Based on these findings, the isolated Lactobacillus rhamnosus displayed promising probiotic characteristics, highlighting human milk as a potential source of these beneficial bacteria